C(n)=15n+90

Simple and best practice solution for C(n)=15n+90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for C(n)=15n+90 equation:


Simplifying
C(n) = 15n + 90

Multiply C * n
nC = 15n + 90

Reorder the terms:
nC = 90 + 15n

Solving
nC = 90 + 15n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-15n' to each side of the equation.
-15n + nC = 90 + 15n + -15n

Combine like terms: 15n + -15n = 0
-15n + nC = 90 + 0
-15n + nC = 90

Reorder the terms:
-90 + -15n + nC = 90 + -90

Combine like terms: 90 + -90 = 0
-90 + -15n + nC = 0

The solution to this equation could not be determined.

See similar equations:

| -40z^5+30z^4+25z^3= | | 8x-(5x+4)=4x-33 | | t-7-29=419 | | 8+3(4y+5)= | | 20x+15y=250 | | 9x+5=3x+1 | | -6x+9-3(x-1)=-(5x-7)-3x+3 | | 20y+15y=250 | | 2x-1x-1x-3x= | | 16b^3+52b^2-48b= | | 8x+8-6x=3+x+1 | | cp^2+-1dp=k | | -0-24=8+0 | | -[10x-(20x+7)]=7+(9x+10) | | 27x-1=15x-72x+7 | | 6x-3(10-x)= | | 27x-1=15x | | 9x-3(3-2x)=5(x-4)-29 | | 638=n-134 | | x(x+1)-380=0 | | 638=n+34 | | w^2+25w-750=0 | | 21x^2-11x+40=0 | | 6(-2+7k)=-12-4k | | 3(3y-1)(2y)=4 | | 3x-(4x-4)= | | 4x+3(x-6)=4(x-3) | | 15s^2-34s+15= | | 1/4w-5=-3 | | 123+k=649 | | 14x+19x-8+1=-2x+1-8 | | 3-2i=-5 |

Equations solver categories